1963
DOI: 10.1111/j.1748-1716.1963.tb02729.x
|View full text |Cite
|
Sign up to set email alerts
|

Primary Afferent Depolarization Evoked from the Sensorimotor Cortex

Abstract: CARPENTER: D., A. LUNDBERG and U. NORRSELL. Primary afferent depolarization evoked from the sensorimotor cortex. Acta physiol. scand. 1963. 59. 126-142. -Stimulation of the sensorimotor cortex evokes dorsal root potentials (DRP) in the lumbo-sacral cord. Primary afferent depolarization is evoked in group I b and group I1 muscle afferents and cutaneous afferents but not in Ia afferents. The effects are mediated by the pyramidal tract. There is spatial facilitation between the paths from primary afferents and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
75
0

Year Published

1973
1973
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 153 publications
(79 citation statements)
references
References 23 publications
4
75
0
Order By: Relevance
“…Segmental hind limb reflexes located in the lumbar spinal cord are heavily influenced by descending and ascending pathways (Carpenter, et al, 1966, Chen, et al, 2001. When these pathways are disrupted after spinal cord injury (SCI), abnormalities of the local lower limb reflexes often develop (Hornby, et al, 2004, Thompson, et al, 1992.…”
Section: Introductionmentioning
confidence: 99%
“…Segmental hind limb reflexes located in the lumbar spinal cord are heavily influenced by descending and ascending pathways (Carpenter, et al, 1966, Chen, et al, 2001. When these pathways are disrupted after spinal cord injury (SCI), abnormalities of the local lower limb reflexes often develop (Hornby, et al, 2004, Thompson, et al, 1992.…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear at present whether monoaminergic or non-monoaminergic systems are involved in these actions (see Discussion of Riddell et al 1992). Terminals of group I a afferents are negligibly affected by such stimuli, although terminals of group I b afferents may be depolarized by stimuli applied in some of the raphe nuclei and in the neighbouring reticular formation (see Carpenter, Engberg & Lundberg, 1966;Rudomin, Jimenez, Solodkin & Duenas, 1983). It is thus possible that the presynaptic inhibition of transmission from I b afferents was responsible for producing the depression of disynaptic I b IPSPs that was sometimes observed in the present experiments following stimulation on the KF and raphe nuclei.…”
Section: The Site Of the Depressive Actionsmentioning
confidence: 99%
“…9,10,15,65,66 So far as the inhibitory aspects of MRF function are concerned, MRF-induced generalized motor inhibition was associated with postsynaptic inhibition of MNs 37,41,42,64,66,68 and presynaptic inhibition of primary afferents. 8 These inhibitory effects were mediated by inhibitory interneurons. 8,37,64,66 Spike-triggered averaging studies demonstrated that a particular group of reticulospinal neurons in the nucleus reticularis gigantocellularis (NRGc), which descended in the ventrolateral funiculus, induced IPSPs in hindlimb MNs located in multiple levels of the lumbosacral segments.…”
mentioning
confidence: 99%
“…8 These inhibitory effects were mediated by inhibitory interneurons. 8,37,64,66 Spike-triggered averaging studies demonstrated that a particular group of reticulospinal neurons in the nucleus reticularis gigantocellularis (NRGc), which descended in the ventrolateral funiculus, induced IPSPs in hindlimb MNs located in multiple levels of the lumbosacral segments. 64,66 Analyses of the triggered IPSPs led to the conclusion that the inhibition is mediated by interneurons located in each level of the 6 lumbosacral segments.…”
mentioning
confidence: 99%